Perancangan Prototype Sistem Monitoring Ternak Ruminansia dengan Metode Human Centered Design - Putriana, Rena; Pradini, Risqy Siwi; Haris, M. Syauqi (LPPM STT Terpadu Nurul Fikri, 2025)
The ruminant livestock sector, such as sheep and cattle, makes a significant contribution to food security and the national economy. However, livestock data management, which is still carried out manually, remains a major challenge in improving operational efficiency, as seen in the Sarwa Adem Mulya (SAM) Cooperative. This study aims to design a prototype of a mobile-based livestock monitoring system called Ruminant Watch, using the Human-Centered Design (HCD) approach to align with the needs and limitations of field users. The research was conducted through five main stages: literature review, specification of the usage context, identification of user needs, design solution development using Figma, and usability evaluation through the System Usability Scale (SUS) questionnaire. The testing results showed an average SUS score of 87, which falls into the “Excellent” category. This indicates that the developed prototype system is not only easy to use but also relevant and effective in supporting livestock monitoring activities. This design is expected to serve as an initial step toward the digitalization of ruminant farming that is more efficient and adaptive to users’ capabilities.